2021
DOI: 10.2478/afpuc-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Thin-layer hydration method to prepare a green tea extract niosomal gel and its antioxidant performance

Abstract: This study aimed to prepare a niosomal gel of green tea (Camellia sinensis) extract containing catechins, mostly epigallocatechin-3-gallate (ECGC), as a potent antioxidant. Niosomes can increase EGCG's stability and penetration into the skin for a better therapeutic effect. Niosomes were prepared by a thin-layer hydration method, were evaluated for their vesicle shape, particle size, polydispersity index, zeta potential and entrapment efficiency, and then incorporated into gels using sodium alginate as a gelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In the current research, the ultra-centrifugation assay was used to evaluate the EE% of VAN-niosome. Firstly, 2 ml of niosomal formulation was centrifuged at 7,500 g at 25 °C for 25 min in an ultra Amicon tube [ 49 ]. Subsequently, the OD of the supernatant was calculated with a UV spectrophotometry (Jasco V-530, Japan) at 281 nm, and the specific amount of free VAN was estimated by a standard curve equation [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the current research, the ultra-centrifugation assay was used to evaluate the EE% of VAN-niosome. Firstly, 2 ml of niosomal formulation was centrifuged at 7,500 g at 25 °C for 25 min in an ultra Amicon tube [ 49 ]. Subsequently, the OD of the supernatant was calculated with a UV spectrophotometry (Jasco V-530, Japan) at 281 nm, and the specific amount of free VAN was estimated by a standard curve equation [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results of the viscosity test of Ageratum leaf hydrogel (Ageratum conyzoides L.) showed that the viscosity test results at FAE 1, FAE 2, and FAE 3 showed good viscosity test results (Table 4) because they were still in the appropriate viscosity range literature (Chasanah et al, 2021). Statistic analysis for the formula didn't show a different result (p > 0.05).…”
mentioning
confidence: 99%